2021
DOI: 10.1016/j.pmedr.2021.101386
|View full text |Cite
|
Sign up to set email alerts
|

Czech adolescents’ remote school and health experiences during the spring 2020 COVID-19 lockdown

Abstract: Highlights One in five adolescents reported economic disruptions during spring 2020 lockdown. Girls and older adolescents reported the worst social and mental well-being. Perceived change in sleep and physical activity varied by gender and behavior. Adolescents reported consuming more fruits and vegetables and less energy drinks. Findings can be used for time trends that include the lockdown period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 40 publications
(44 reference statements)
5
32
0
1
Order By: Relevance
“…However, our findings are not similar to those of previous studies [ 22 , 23 , 24 , 25 ] that demonstrated a significant decrease in physical activity in children after the emergency declaration compared to that in children before the emergency declaration. In the present study, the total time of physical activity increased among children in Japan, which is in line with the results of studies from Belgium, the Czech Republic, Germany, and Spain [ 26 , 27 , 28 , 29 ]. Thus, different behaviors of children from different countries might be due to factors such as differences in policy restrictions and the number of COVID-19 infections found in children [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, our findings are not similar to those of previous studies [ 22 , 23 , 24 , 25 ] that demonstrated a significant decrease in physical activity in children after the emergency declaration compared to that in children before the emergency declaration. In the present study, the total time of physical activity increased among children in Japan, which is in line with the results of studies from Belgium, the Czech Republic, Germany, and Spain [ 26 , 27 , 28 , 29 ]. Thus, different behaviors of children from different countries might be due to factors such as differences in policy restrictions and the number of COVID-19 infections found in children [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…This discrepancy is perhaps due to age differences since our study evaluates PA in children 8–12 years old, while the study by Ng was done on older children aged 11–15 years at a different time of year. We collected data in November-January, while Ng collected their data from May-June, when more individual outdoor PA could be expected [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…while Ng collected their data from May-June, when more individual outdoor PA could be expected [48].…”
Section: Plos Onementioning
confidence: 99%
“…In line with our second hypothesis, we found that adolescents’ perceived stress was associated with greater decrease in school bonding, whereas adolescents’ perceived coping was associated with less decline in school bonding. Early research on the pandemic revealed that adolescents were stressed about school closures, virtual learning, and diminished peer relationships at school (Ellis et al., 2020 ), which was associated with greater social isolation and loneliness (Larsen et al., 2021 ; Ng et al., 2021 ). Yet, many adolescents also coped with these unprecedented stressors by problem‐solving and seeking support (Duan et al., 2020 ; Ellis et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given that school bonding is thought to be malleable and responsive to environmental conditions (Allen et al., 2018 ), it is possible that school‐related disruptions due to the COVID‐19 pandemic could alter youths' school bonding. Recent research, for example, has linked pandemic‐related school closures and virtual learning to feelings of social isolation and loneliness among adolescents (Larsen, Helland, & Holt, 2021 ; Ng, Cosma, Svacina, Boniel‐Nissim, & Badura, 2021 ). In the present study, we explored how school bonding changed during a pandemic that necessitated that adolescents stay home and move to online learning environments.…”
Section: Introductionmentioning
confidence: 99%